Preliminary study on guideline on soil health quality index of fluorine and method of its evaluation in China - LI Jing; XIE Zheng-miao; XU Jian-ming; WU Wei-hong (浙江大学学报. 农业与生命科学版, 2005)
Based on related data of incidence of local fluoride epidemic and fluorine concentration in soils in China as seen in literature published in China, the relationship between soil environmental quality of fluorine and human health in China was reviewed and analyzed in the present paper, with the results that guideline on soil environmental quality of fluorine in relation to human health, including guideline on total and water soluble fluorine content of soils, as well as the assessing methods for predicting local fluoride epidemic, were established.